Dams in the Mekong Basin: Commissioned, Under Construction and Planned Dams in May 2013 - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
Shows all known dams in the Mekong Basin (commissioned, under construction and planned) as at May 2013. 'Unknown' dams are mainly dams and reservoirs constructed for use in irrigation and water supply, the names of which are current unknown. Data sources: Citation of the data sources contributing to the location of the dams in this map may be found at www.mekong .waterandfood.org/archive/2648